Leicht erhoehte temperatur 4000D : eine Ausstellung aktueller Kunst aus Düsseldorf. - Schloss Parz, Grieskirchen/Oberösterreich (Düsseldorf : [s.n.], 1987)
Dekovic, Ivo ; Klepsch, Axel ; Geismar, Jarg M ; Post, Oliver ; Iacob, Ioan ; Imbach, Samuel ; Sery, Christian ; Luy, Wolfgang ; Lenhart, Johannes ; Mundt, Wilhelm ; Lepper, Gereon ; Hardung, Marcel ; Mahn, Inge ; Wünkhaus, A.S. ; etc.
Leicht erhoehte temperatur 4000D : eine Ausstellung aktueller Kunst aus Düsseldorf, Schloss Parz, Grieskirchen/Oberösterreich, 1987
boek